An alternative application of imagery in youth sport: Promoting the transfer of life skills to other contexts. Issue 1 (2nd January 2016) - Jacobs, Jenn M.; Wright, Paul M.
Abstract: Significant sport psychology research has been devoted to the positive effects that sport participation can have on youth outcomes, including social, emotional, and physical skills (Gould & Carson, 2008 ; Petitpas, Cornelius, Van Raalte, & Jones, 2005 ). Central to this concept is the idea that learning that occurs during sport participation will actually transfer these valuable life skills to other non-sport contexts in a youth's life (Danish & Nellen, 1997 ). This article proposes imagery as one potential strategy for facilitating this transfer of learning process from a youth development framework. Several practical suggestions for youth coaches on the application of imagery techniques for life skill utilization in and out of sport are discussed.